Causal relationship between iron deficiency anemia and asthma: a Mendelian randomization study - Li, Mengchun; Chen, Zhengdong; Yang, Xin; Li, Wanwei (Frontiers in Pediatrics, 2024)
Background Observational studies have suggested an association between iron deficiency anemia (IDA) and asthma, which may affect the occurrence of asthma. However, whether IDA is a new management goal for asthma remains to be determined. Objective We conducted a two-sample Mendelian randomization(MR)analysis to assess the association between IDA and asthma. Methods We performed a two-sample MR study to assess a causal relationship between IDA (ncase = 12,434, ncontrol = 59,827) and asthma (ncase = 20,629, ncontrol = 135,449). Inverse variance weighted (IVW) was used as the primary method for the analyses. Furthermore, we used weighted medians and MR-Egger to enhance robustness. Data linking genetic variation to IDA and asthma were combined to assess the impact of IDA on asthma risk. Results There are five single nucleotide polymorphisms (SNPs) were used as genetic tool variables for exposure factors. Genetically determined IDA was significantly associated with an increased risk of asthma (OR = 1.37, 95% CI: 1.09–1.72, p = 0.007). There was little heterogeneity in the MR studies and no evidence of level pleiotropy was found. Conclusions In our MR study, our findings emphasize that IDA may be associated with a high risk of asthma, indicating a potential role for IDA in the development of asthma. Future research needs to elucidate its potential mechanisms to pave the way for the prevention and treatment of asthma.